2021
DOI: 10.1108/mrjiam-01-2021-1129
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment in call centers and customer satisfaction

Abstract: Purpose Call center is a large and growing sector worldwide and is facing important human resource management (HRM) and service challenges. The purpose of this study is to analyze the impact of structural empowerment (SE) and psychological empowerment (PE) on customer satisfaction (CS) through employee job satisfaction (JS) at a call center in Portugal. Design/methodology/approach Data were collected by means of a survey handed over personally to 267 employees at the call center of a telecommunication compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Russell (2008, p. 200) suggested that, “in order to provide the services they are called upon to deliver, frontline workers in general and call-centre employees in particular require enhanced levels of decision-making autonomy”. Furthermore, Proenca and Rodrigues (2021) revealed that the compensation and discretionary autonomy of operators are linked to their job satisfaction and customer satisfaction. In addition, all call centre directors understood that issues remained unresolved.…”
Section: Resultsmentioning
confidence: 99%
“…Russell (2008, p. 200) suggested that, “in order to provide the services they are called upon to deliver, frontline workers in general and call-centre employees in particular require enhanced levels of decision-making autonomy”. Furthermore, Proenca and Rodrigues (2021) revealed that the compensation and discretionary autonomy of operators are linked to their job satisfaction and customer satisfaction. In addition, all call centre directors understood that issues remained unresolved.…”
Section: Resultsmentioning
confidence: 99%
“…Satisfaction involves cognitive and affective processes and other psychological influences (Rather, 2018; Rehman et al , 2020; Utami et al , 2021). A commonly used definition of satisfaction adopts a disconfirmation perspective of consumer satisfaction or dissatisfaction, suggesting that satisfaction results from interaction and post-evaluation (Bilro and Loureiro, 2021; Proenca and Rodrigues, 2021). In this study, we follow the view that satisfaction increases the possibility of future intentions (Rather, 2018; Thomas et al , 2002).…”
Section: Theoretical Backgroundmentioning
confidence: 99%